0994 Thematic, Content and Policy Analysis of Sleep Health Promotion in Social Service Policies Impacting The Most Vulnerable Children In The United States. (12th April 2019) - Pandey, Abhishek; Littlewood, Kerry; Carter, Shima; Rosenthal, Michelle; Bennett, Russell; Cooper, Lawrence
Abstract: Introduction: Social services are the nation's system of programs, benefits, and services that help people meet those social, economic, educational, and health needs. Using a social justice framework and building on our previous review of sleep in child welfare, we were interested in learning how healthy sleep was integrated into program policies and manuals serving the most vulnerable children and families in the US to recommend areas for future intervention. Methods: KL & SC conducted a systematic review, thematic and content analysis of 513 administrative program policies and manuals from large social service systems with programs serving over 22.3 million vulnerable children and families facing adverse childhood experiences and health disparities. A systematic review assessed for the inclusion of healthy sleep education or promotion methods. Bardach's eightfold path method of policy analysis was used to examine policy options related to healthy sleep promotion and identify targets for intervention. Results: Healthy sleep was included in only 7 (1%) policies in Special Supplemental Nutrition (WIC), Healthy Start, Head Start, Children's Health Insurance, Child Welfare, and Juvenile Justice programs targeted in this review. Healthy start provided the most mentions (4) of healthy sleep in manualized educational information, related to infant safe sleep. Child welfare and juvenile justice policy advised on compliance-driven sleep standards, such as providing available space and bed to children and youth. The policy analysis identified benefit re-enrollment, intake, home visits, home safety assessments, family team meetings, and case closure visits as the most viable touchpoints for sleep promotion in social policy. Conclusion: Although Healthy Start included infant safe sleep, no other programs provided healthy sleep education or promotion for older children above 5 years of age. Intentionally integrating healthy sleep education and promotion into existing programs may be an important way to reach over 22.3 million vulnerable children and families. Future studies could use the policy recommendations of this study to improve the integration of healthy sleep into our training and social policy practice. Support (If Any): N/A